A Critical Study of the Loss and Gain of the Lost Generation - Shahriar Choubdar (MA), Seyedeh Zahra Nozen, (Opción, 2019)
This study aims to the evaluation of the features of the group of writers who chose Paris as their new home to produce their works and the overall dominant atmosphere in that specific time in the generation that has already experienced war through comparative research methods. As a result, writers of this group tried to find new approaches to report different contexts of modern life. As a conclusion, regardless of every member of the lost generation bohemian and wild lifestyles, the range, creativity, and influence of works produced by this community of American expatriates in Paris are remarkable.